Energy factor and mathematical modelling of power DC/DC converters - Win Latt Latt. (2009)
Energy storage in power DC/DC converter has been paid attention long time ago and the application of the traditional mathematical factors such as power factor(PF),power transfer effciency,total harmonic distortion (THD) and ripple factor (RF) of the power DC/DC converters have achieved a great success to describe the characteristics of power systems.Unfortunately,all these factors are not available to use to describe the other high frequency switching circuits,high number of passive components due to requirement to manipulate higher order differential equations. The main objective of this final year project is introduced a new mathematical modelling method based on the concept of Energy Factor which is different from the traditional factors, introduced a very simple approach for deriving a better model DC/DC converters.